Clinical Predictors of Histologic Chorioamnionitis at Term [06N]. (May 2020) - Romagano, Matthew P.; Pinho, Gabriella; Krishnamoorthy, Kaila; George, Lea; Williams, Shauna F.; Apuzzio, Joseph
Abstract : INTRODUCTION: The objective of this study was to determine the diagnostic criteria for clinical chorioamnionitis (CC) that best predict histologic chorioamnionitis (HC). METHODS: This is an IRB-approved retrospective cohort study of women diagnosed with CC over a 5-year period. Inclusion criteria were: gestational age 37 to 42 weeks, diagnosis of CC as determined and documented by the provider, and available placental pathology records. CC diagnostic criteria (maternal temperature, maternal or fetal tachycardia, leukocytosis, fundal tenderness, and purulent amniotic fluid) were compared between those with and without HC. RESULTS: 223 women met inclusion criteria; 159 (71.3%) had HC. Prostaglandin use, diabetes, epidural use, and duration from initiation of antibiotics to delivery were similar. Mean maximum body temperature and presence of other diagnostic criteria were similar between the groups. Those with HC were more likely to have a peak white blood cell count greater than or equal to 25.0x10^9cells/L (13.2 vs 3.1%, P= .03). Twenty-one (13.2%) women in the HC group and 12 (18.8%) in the normal pathology group had no documented fever despite a diagnosis of CC. Of the women without a fever, 64% had HC. CONCLUSION: Normal placental pathology was found in a large proportion of women with CC. Although none of the assessed clinical findings predicted HC, a significant leukocytosis was more frequent in women with HC. For women diagnosed with CC without fever, the majority had findings of HC. This study highlights the challenge of diagnosing CC. Providers should consider the diagnosis of CC in the absence of fever when other clinical criteria are present.